The study on Organizational Structure and demographic profile of Farmer Producer Organisations (FPOs): A Case Study from Himachal Pradesh - Sharma, Ashima; Raina, K K; Panta, Razal (International Journal of Engineering and Management Research, 2025)
This study examines the organizational structure and functioning of Farmer Producer Organizations (FPOs) in Himachal Pradesh, with a focus on their role in improving farmers’ market access, profitability, and operational efficiency. The research was conducted in four districts—Shimla, Solan, Sirmour, and Kinnaur—where commercial fruit and vegetable farming is dominant. Seven FPOs were selected based on their engagement in fruit and vegetable cultivation and their resource support agencies, either Small Farmers’ Agri-Business Consortium (SFAC) or Himachal Pradesh Horticulture Development Project (HPHDP). Findings reveal that the FPOs operate within a four-tier organizational structure comprising farmer shareholders, farmers' interest groups, a representative general body, and board members. The key objectives of these FPOs include collective procurement, technological advancement, price enhancement, advisory services, training, and improved access to agricultural inputs and markets. Their primary functions span collective marketing, sorting, grading, packaging, transportation, and exposure visits. While some FPOs actively pursue technological advancements and improved market access, others are confined to specific objectives. The study suggests strengthening governance mechanisms and providing a simplified administrative framework to enhance the effectiveness of FPOs. Additionally, expanding the research to other districts and states can offer deeper insights for policy formulation and improving the sustainability of FPOs.